2015 International Conference on Data and Software Engineering (ICoDSE) 2015
DOI: 10.1109/icodse.2015.7436977
|View full text |Cite
|
Sign up to set email alerts
|

Developing a game for preschoolers: What character, emotion and reward will tend to hack preschoolers?

Abstract: Games can be evolved into a creature that can condition the users enjoy doing activities especially for the kids. User interface elements are a major factor to attract kids to play. This subject aim to identify the preschoolers' propensity to game's user interface, particularly the character, emotion and reward. The method applied is the research and development focusing on the user interface necessity analysis in the game with survey. The tendency of character, emotion and reward game that can captivate presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
2
0
4
Order By: Relevance
“…Wang and Sun [221] articulated those rewards can deliver pleasure and satisfaction to players. Rewards also showed a positive influence on adding the enjoyable factor for the players [222], which consequently impacts the intrinsic motivation [223]. A psychological study found that rewards in gamification systems can increase customers' loyalty to their vendors [224].…”
Section: Psychologymentioning
confidence: 99%
“…Wang and Sun [221] articulated those rewards can deliver pleasure and satisfaction to players. Rewards also showed a positive influence on adding the enjoyable factor for the players [222], which consequently impacts the intrinsic motivation [223]. A psychological study found that rewards in gamification systems can increase customers' loyalty to their vendors [224].…”
Section: Psychologymentioning
confidence: 99%
“…Simi memiliki 7 kesempatan untuk menyelesaikan permainan dan apabila kesempatan sudah habis, simi harus mengulangi permainan dari awal. Ekspresi kemenangan karakter yang mendapat reward dapat meningkatkan energi dan membuat permainan menjadi lebih menyenangkan [7], Player memiliki 10 kesempatan yang akan berkurang 1 jika nyawa player habis. Apabila kesempatan habis, maka permainan akan berakhir dengan kekalahan.…”
Section: Perancangan Aplikasi 1 Storylineunclassified
“…Dalam suatu game anak cenderung di berikan suatu Reward (Penghargaan) untuk menstimulasi anak agar lebih tertarik memainkan game tersebut [10] dan dalam aplikasi ini peneliti menggunakan bintang, score dan audio Exelent sebagai reward untuk anak. Dalam penelitian ini penulis menjelaskan bahwa pada tahap pertama user menggunakan aplikasi game tersebut akan di tujukan pada halaman Menu yang mana user dapat memilih icon Buah, Sayur, Hewan dan Petunjuk yang akan menjelaskan cara bermain.…”
Section: Storylineunclassified